Environmental adaptability, morphometric features with reproductive and productive potentialities of indigenous sheep in Bangladesh - Rakib, Md Rezaul Hai; Desha, Nure Hasni; Rahman, Md Zillur; Kabir, Md Ahsanul; Yasmin, Farzana; Alam, Md Ashadul; Akther, Sonia; Sultana, Nasrin (Journal of Advanced Veterinary and Animal Research, 2022)
Indigenous sheep are highly adaptable and widely distributed in different regions of Bangladesh. They are famous for their tolerance to harsh environmental conditions, low demand for feed, and disease resistance with minimum or no housing and management facilities. Ample indiscriminate research reports and case studies on the native sheep of Bangladesh have been published. Nonetheless, a comprehensive review of reproductive and productive performances, as well as their various morphometric physiognomies and climate resilience capabilities, is lacking. This review was designed to explore and summarize the available research reports on indigenous sheep to highlight the gaps and provide an updated database for the future research plan for sustainable native sheep production in Bangladesh. It covers studies on sheep biodiversity, their adaptability to the local environment, morphometric features, feeding and nutrition, reproduction and production performances, diseases and health management, and the problems and prospects of sheep farming in Bangladesh. Due to the increased demand for animal protein, especially red meat, the scope of sheep farming increases along with that of other large and small ruminants. The vital constraints of sheep production in Bangladesh include insufficient feed and fodder supply with its high prices, higher disease occurrence with low or no management practices, kid mortality, and a poor marketing channel with the lower popularity of sheep meat than goat meat. Future research would be a prerequisite to measuring the impact of native sheep on household economies and food security during the year, evaluating the other challenges, and finding out the possible interventions in the fields of nutrition, reproduction, and health management. J. Adv. Vet. Anim. Res., 9(4): 649–662, December 2022 http://doi.org/10.5455/javar.2022.i634